Biopolymer and polymer precursor production by microorganisms: applications and future prospects - Saharan, Baljeet Singh; Kamal, Neel; Badoni, Prerana; Kumar, Ramesh; Saini, Mayuri; Kumar, Dharmender; Sharma, Deepansh; Tyagi, Swati; Ranga, Poonam; Parshad, Jagdish; Goyal, Chhaya; Kumar, Ravinder; et al. (Wiley, 2024)
Polymers have been used in various industries over the past few decades due to their tremendous applications. Among these, polyhydroxyalkanoates and poly(lactic acid) are easily biodegradable biopolymers derived from bacteria, including recombinant Escherichia coli, Alcaligenes eutrophus, Alcaligenes latus, Azotobacter vinelandii, methylotrophs and Pseudomonas. Conventional petroleum‐derived polymers have become potentially harmful to the environment due to their complex degradation process. The nonbiodegradability of synthetic polymers has become a global issue of concern. There is an urgent need for a substitute to tackle the increasing environmental stress. Microorganisms are small factories for producing different types of polymers during their growth cycle. Various features like biodegradability, biocompatibility, nontoxicity and wide substrate spectrum make such microbial polymers highly reliable. Biopolymers such as alginate, cellulose, cyanophycin, levan, polyhydroxyalkanoates, xanthan, poly(lactic acid) and poly(γ‐glutamic acid) can be obtained from different microorganisms like Aureobasdium pullulans, Acetobacter xylinum, Bacillus thermoamylovorans and Cupriavidusnecator. These are extensively used in various fields like food, medicine, wastewater treatment, biofuel production, packaging and cosmetics. Despite being advantageous in several ways, the biopolymer market still faces several hurdles. This review mainly emphasizes the different types of biopolymers, production by microorganisms and various applications of these biopolymers in different fields. The main drawback limiting the development of these polymers is the high production cost and low efficiency of the microbial strains. Genetic recombination is an efficient technique to enhance the microbial yield and to expand the biopolymer market size. © 2023 Society of Chemical Industry (SCI).